Electrosynthesis of Metal–Organic Frameworks: Challenges and Opportunities. Issue 4 (20th March 2015) - Al‐Kutubi, Hanan; Gascon, Jorge; Sudhölter, Ernst J. R.; Rassaei, Liza
Abstract The front cover artwork is provided by the Organic Materials & Interfaces and Catalysis Engineering Groups at Delft University of Technology (The Netherlands). The image shows the electrosynthesis of a metal–organic framework (MOF) when using anodic dissolution. The metal ions, released through electrode oxidation, combine with the linker to form the final frameworks. Read the full text of the Article at 10.1002/celc.201402429.